2014
DOI: 10.1016/j.seizure.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of vagal nerve stimulation in a pediatric population: A single center experience

Abstract: VNS provides significant seizure reduction, in particular in pediatric patients with a higher baseline seizure frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
2
16
0
3
Order By: Relevance
“…We found that VNS therapy contributed to notable reduction of seizure burden in nearly half of patients (Fig. 1), and 33% of our patients responded with ≥50% reduction of seizure frequency after 12 months of therapy, which is similar to many other studies ( 9 , 10 , 12 , 17 , 19 ), while some authors have reported better efficacy ( 16 , 20 - 23 ). The response rate in our patients should be considered from two aspects: firstly, the majority of our patients had severe drug-resistant epilepsy for a very long time before VNS, and some studies indicated that longer duration of epilepsy could be negatively correlated with the efficacy of VNS ( 24 ).…”
Section: Discussionsupporting
confidence: 89%
“…We found that VNS therapy contributed to notable reduction of seizure burden in nearly half of patients (Fig. 1), and 33% of our patients responded with ≥50% reduction of seizure frequency after 12 months of therapy, which is similar to many other studies ( 9 , 10 , 12 , 17 , 19 ), while some authors have reported better efficacy ( 16 , 20 - 23 ). The response rate in our patients should be considered from two aspects: firstly, the majority of our patients had severe drug-resistant epilepsy for a very long time before VNS, and some studies indicated that longer duration of epilepsy could be negatively correlated with the efficacy of VNS ( 24 ).…”
Section: Discussionsupporting
confidence: 89%
“…3,7 Beyond the seizure outcome, the study demonstrated the success of a model that integrates service with business, teaching, and research. The outcome of neuromodulation may be confounded by titration of medications that was performed by the referring physician.…”
Section: Discussionmentioning
confidence: 92%
“…3,5,7 The challenge ahead of us is to integrate these different therapies in busy clinical practice. 3,5,7 The challenge ahead of us is to integrate these different therapies in busy clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was no statistically significant predictor of outcome in the ≥ 50% responder analysis. Several studies also could not determine the predictors of outcome based on demographic characteristics [23,32]. This is probably due to the ambiguous mechanism of VNS and widespread projection fibers of the nucleus solitarius tract, which is a transfer center of the vagus nerve [20].…”
Section: Discussionmentioning
confidence: 99%